EXPRESSION AND PURIFICATION CAPSID PROTEINS VP0, VP1 AND VP3 OF FOOT AND MOUTH DISEASE VIRUS TYPE O IN ESCHERICHIA COLI - Duong, Nguyen Hoang; Chuang, Chi-Ning; Hoa, Nguyen Phuong; Dung, Tran Thi Kim; Minh, Le Hong; Anh, Nguyen Mai; Kim Cuc, Nguyen Thi; Ha, Le Thu; Cuong, Pham Viet; Fang, Ting-Wang (Vietnam Journal of Science and Technology, 2016)
Foot and mouth disease virus (FMDV) causing infectious disease affects broadly cloven-hoofed animals. It has 7 different serotypes. However O is the most prevalent type in 3 founded types (O, A, Asia1) recurrence in Vietnam fields. The current vaccine for FMDV is inactivated or attenuated forms. Vaccines were able to raise strong immune responses but still caused the safety concerns. Virus-like particles could be a new vaccine generation that fulfills the present questions. On the one hand, it can tackle the safety issues, on the other hand, it can reserve FMDV intrinsic form which will provoke high immunogenicity. The important initial step to make virus-like particles is expression the capsid proteins of FMDV in appropriate system. So this study we describe how to design, express and purify of all capsid proteins: VP0, VP1 and VP3 of O type FMDV isolated in Vietnam field using SUMO fusion expression system.